Research of Detection and Quantitative method of Cypermethrin, Fenvalerate and Deltamethrin Residues in Sediment by Gas Chromatography. Issue 4 (February 2019) - Tian, Liangliang; Kong, Cong; Fang, Changling; Lou, Xiaoyi; Han, Feng; Shi, Yongfu; Cai, Youqiong
Abstract: A gas chromatography method was developed for the quantification and identification of cypermethrin, fenvalerate, and deltamethrin residues in sediment with electron capture detector (ECD). Homogenized samples were extracted by N-hexane/dichloromethane (1/1), desulfurization with copper powder. The samples were cleaned up by silica solid phase extraction (SPE) cartridge. There were many isomers in cypermethrin and fenvalerate, but the proportions of different isomers were different in different concentrations, so it was more accurate to quantify by the total quantity. The analytes were quantified by the standard materials dissolved in matrix solution. Under optimal experimental conditions, good linearity was observed in the range of 20∼2000 ng/mL for cypermethrin, fenvalerate and 2∼200 for deltamethrin, the correlation coefficients were 0.9984∼0.9991. The results showed that the limit of quantitation (LOQ) was 0.4～4 μ g/kg. The recovery and RSDs of three-level spiked samples were in the ranges of 83.2%～92.1% and 3.2% ～8.5%. This method is highly effective to reduce time for pretreatment of sample, and the result showed that was accurate to detect the cypermethrin, fenvalerate, and deltamethrin residues in sediment.